Novel role of platelet reactivity in adverse left ventricular remodelling after ST-segment elevation myocardial infarction: The REMODELING Trial - Park, Yongwhi; Tantry, Udaya S.; Koh, Jin-Sin; Ahn, Jong-Hwa; Kang, Min Gyu; Kim, Kye Hwan; Jang, Jeong Yoon; Park, Hyun Woong; Park, Jeong-Rang; Hwang, Seok-Jae; Park, Ki-Soo; Kwak, Choong Hwan; Hwang, Jin-Yong; Gurbel, Paul A.; Jeong, Young-Hoon (Thrombosis and Haemostasis, 2017)
The role of platelet-leukocyte interaction in the infarct myocardium still remains unveiled. We aimed to determine the linkage of platelet activation to post-infarct left ventricular remodelling (LVR) process. REMODELING was a prospective, observational, cohort trial including patients (n = 150) with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention. Patients were given aspirin plus clopidogrel therapy (600 mg loading and 75 mg daily). Platelet reactivity (PRU: P2Y12 Reaction Units) was assessed with VerifyNow P2Y12 assay on admission. Transthoracic echocardiography was performed on admission and at one-month follow-up. The primary endpoint was the incidence of LVR according to PRU-based quartile distribution. LVR was defined as a relative ≥ 20 % increase in LV end-diastolic volume (LVEDV) between measurements. Adverse LVR was observed in 36 patients (24.0 %). According to PRU quartile, LVR rate was 10.8 % in the first, 23.1 % in the second, 27.0 % in the third, and 35.1 % in the fourth (p = 0.015): the optimal cut-off of PRU was ≥ 248 (area under curve: 0.643; 95 % confidence interval: 0.543 to 0.744; p = 0.010). LVR rate also increased proportionally according to the level of high sensitivity-C reactive protein (hs-CRP) (p = 0.012). In multivariate analysis, the combination of PRU (≥ 248) and hs-CRP (≥ 1.4 mg/l) significantly increased the predictive value for LVR occurrence by about 21-fold. In conclusion, enhanced levels of platelet activation and inflammation determined the incidence of adverse LVR after STEMI. Combining the measurements of these risk factors increased risk discrimination of LVR. The role of intensified antiplatelet or anti-inflammatory therapy in post-infarct LVR process deserves further study.
Keywords: Myocardial infarction; LV remodelling; platelet reactivity; inflammation